A Review on the Great Game in Afghanistan: A Realist Perspective on the Geopolitical Struggle for Control (Journal of International Relations and Peace, 2024)
This review aims to analyze the Great Game in Afghanistan from a realist perspective, focusing on the geopolitical struggle for control among major powers. The study delves into historical events and power dynamics to comprehend the motivations and actions of key actors. The Great Game in Afghanistan refers to the historical rivalry and strategic competition between great powers for regional influence and control. This review adopts a realist perspective, which asserts that states act primarily in their own self-interest and pursue power and security in international relations. The methods employed include historical analysis and comparative analysis, providing comprehensive information on the Great Game in Afghanistan and examining key events, diplomatic maneuvers, and power dynamics. The results shed light on the motivations and actions of key actors, highlighting the enduring nature of the Great Game. The Great Game in Afghanistan, involving great powers like the British Empire, the Soviet Union, and the US, has led to instability and hindered Afghanistan’s development as a sovereign nation. The conclusion underscores the significance of power politics in shaping Afghanistan’s trajectory, and the Great Game in Afghanistan highlights the persistent power dynamics in international relations, driven by geopolitical considerations and self-interest, resulting in conflicts and instability. The recommendation emphasizes the need for a nuanced and pragmatic approach to managing the country’s geopolitical dynamics. The Great Game’s historical context calls for a pragmatic approach to managing Afghanistan’s geopolitical struggles, prioritizing regional cooperation, inclusive diplomacy, and economic development for stability and progress.